NEK8 promotes the progression of gastric cancer by reprogramming asparagine metabolism - Wang, Mingliang; Yu, Kexun; Meng, Futao; Wang, Huizhen; Li, Yongxiang (Molecular medicine (Cambridge, Mass.), 2025)
Several members of the NIMA-related kinase (NEK) family have been implicated in tumor progression; however, the role and underlying mechanisms of NEK8 in gastric cancer (GC) remain unclear. This study revealed a significant upregulation of NEK8 in GC, identifying it as an independent prognostic marker in patients with GC. Consistent with these findings, NEK8 silencing substantially impeded GC aggressiveness both in vitro and in vivo, while its overexpression produced the opposite effect. Gene Ontology enrichment analysis and metabolic profiling indicated that the impact of NEK8 on GC is primarily associated with reprogramming asparagine metabolism and modulating the mTORC1 pathway. Specifically, NEK8 knockdown suppressed asparagine synthesis by downregulating asparagine synthetase (ASNS) expression in GC cells. A strong correlation was observed between NEK8 levels and ASNS expression in human GC cells and tissue samples. Mechanistically, NEK8 directly interacts with ASNS, phosphorylating it at the S349 site, which inhibits its ubiquitination and subsequent degradation. Moreover, substituting the ASNS-S349 site with alanine abrogated the pro-tumorigenic effects of ASNS-WT overexpression. Additionally, asparagine was identified as an activator of the mTORC1 pathway, with reintroducing asparagine after NEK8 silencing restoring mTORC1 activity. Collectively, these findings demonstrate that NEK8-mediated asparagine synthesis and activation of the mTORC1 pathway play a critical role in promoting GC progression.